PAHAM KETUHANAN KANG MURBENG DUMADI DALAM RITUAL SELAPANAN DI DESA JOMEGATAN, KASIHAN, BANTUL - Emanuel Yuliman (IN VERITATE LUX, 2025)
Abstract The Selapanan ritual in Javanese tradition is a form of spiritual expression that is very full of meaning, beyond just a cultural celebration. This research aims to explore in depth the understanding of divinity reflected in the selapanan ritual, focusing on the concept of Kang Murbeng Dumadi as the highest entity. The case study was conducted in Jomegatan Village, Kapanewon Kasihan, Bantul, an area that continues to preserve this tradition. Using a qualitative method that combines literature study with in-depth interviews with local culturists, this research examines how theological values are realised through processions and symbols in the selapanan ritual. The results show that the understanding of Kang Murbeng Dumadi as the Creator and Sustainer of life is manifested concretely in ritual symbols. Symbols such as tumpeng symbolise orientation of life to God, the colour of jenang represents spiritual protection (Sedulur Papat Kalimo Pancer), and the lamp symbolises the illumination of the path of life. It is concluded that the selapanan ritual in Jomegatan Village is not only a traditional heritage, but also a medium for the actualisation of a dynamic understanding of divinity, which reflects the harmonious relationship between humans, nature and the Creator in the midst of the times. Despite changes and developments in terms of expression and form, the main essence of selapanan has not changed, which is to ask for safety from the Almighty for the baby's life journey with the family and people around him.